Social Justice for Affective and Sexual Experience in Costa Rica - Fallas Vargas, Manuel Arturo (2016)
In this article, the authors meditate on social justice, sexuality and the link between this these two concepts towards a more inclusive and respectful society. Our approach responds to an educational model centered in the respect of the different types of sexual biographies, starting from the principle that the lack of social justice implies a decrease in the emotional and sexual experience of people. This paper is based on a review and consideration around Costa Rican theory and reality as seen in the current media. There is also a suggestion of a series of good practices and some conclusions for the strengthening of social justice and ergo an emotional and sexual well-being of people.